Can Recombinant Granulocyte Colony Stimulating Factor Modulate Inflammatory Response in Extreme Low Gestational Age Newborns?: Effect of rhG-CSF on Cytokines in ELGAN - Kocherlokata, Prabhakar; Crow, Mary; Vakkalanka, Radhakrihna; La Gamma, Edmund F. (Journal of Pediatric Infectious Diseases, 2017)
Background Elevated levels of cytokines like interleukin-6 (IL-6) and tumor necrosis factor-alpha (TNF-α) are common in critically ill neonates, and may contribute to organ-based injury during acute illness contributing to neurodevelopmental delay. In both animals and human adults, recombinant human granulocyte-colony stimulating factor (rhG-CSF) is associated with a reduction in TNF-α blood levels.Objective We aim to determine whether rhG-CSF treatment affects the blood levels of proinflammatory cytokines, TNF-α and IL-6 or the anti-inflammatory cytokine, IL-10 in extremely-low-gestational age neonates (ELGANs) compared with conventional medical management.Methods The study included three groups of ELGANs between 2 and 4 days of age as subjects. Control group (n = 5); treated, nonseptic group (n = 10); and treated, septic group (n = 5) neonates were treated with conventional measures. In addition, the test subjects were treated with 10 μg/kg/d of rhG-CSF intravenously for 3 consecutive days. The levels of TNF-α, IL-6, and IL-10 were measured before and 24 hours after completion of the study.Results The average TNF-α levels increased after birth in control subjects but did not rise in rhG-CSF treated subjects. A nonsignificant decrease of IL-6 and IL-10 blood levels was noted in all the subjects independent of the drug treatment.Conclusion The use of rhG-CSF is associated with lower TNF-α levels in ELGANs.Speculation During critical illness or sepsis, rhG-CSF may have unanticipated benefits as a drug that can elevate neutrophil number and function in neonates while simultaneously limiting collateral injury due to TNF-α.
Keywords: human recombinant granulocyte colony stimulating factor (rhG-CSF); interleukin-6; interleukin-10; tumor necrosis factor-α; extremely-low-gestational age neonate